Sustainable animal production in Uganda: leveraging private and public sector collaboration - International Livestock Research Institute (2024)
Over the last 10 years, ILRI has worked with the private sector, policymakers, including the Ministry of Agriculture, Animal Industry and Fisheries (MAAIF) and district local governments to promote and build capacity within the pig sector in Uganda.